How the Global Initiative Report's Indicators are Related to the Strong Sustainability Concept? - A Paraconsistent Approach - Langa, Est ^ev ao S.; Agostinho, Feni; Liu, Genguyan; Almeida, Cec ' ilia M.V.B.; Giannetti, Biagio F. (Journal of Environmental Accounting and Management, 2026)
The pressure imposed by human-dominated systems on the natural environment and the search for more balanced social systems are current concerns worldwide. Among scales of attention and shared responsibilities, companies are also in the radar of and interested in to be more sustainable. An efficient way in disclosing information on companies' sustainability is through sustainability reports, such as the global reporting initiative (GRI) framework. Although recognized as an important alternative, the GRI is receiving criticisms about its ability in accurately express the meaning of sustainability. This work applies the paraconsistent annotated evidential logic (PAEL) on opinions of experts in the sustainability theme to verify whether the GRI indicators are aligned to the concept of `strong' sustainability. A survey applied to twenty-two experts from different field areas, backgrounds and work experiences on sustainability-related issues provided their beliefs and disbeliefs, in a quantitative way, about the ability of each of the 91 GRI indicators in expressing sustainability. Results show high dispersion (coefficient of variation $>$30%) among the experts opinions for 77 of the GRI indicators, in which the social category appears with the worst performance with its total 48 indicators with high dispersion. This is an indicative of different understandings by experts about the meaning of sustainability concept and/or the meaning and reach of GRI indicators in achieving sustainability. The PAEL reports that all three categories (economic, environmental and social) fall into the `paracomplete' region of the Cartesian unitary square's graph, indicating an inconclusive result about whether these three categories are able to capture and/or express the concept of strong sustainability. The overall performance (barycenter with beliefs of $μ =0.26$ and disbeliefs of $λ =0.17$) also fall into the paracomplete region, rejecting the initial hypothesis that GRI may show strong sustainability. Recognizing the increasing importance of sustainability reports, this work contributes in identifying and suggesting improvements to the GRI developers on indicators that may better represent the strong sustainability and achieve its main goals. GRI's framework should be based on a clear sustainability model and provide through a simple, fast and understandable way, information about the purposes of each indicator. Focus for improvements should be especially directed to: EC4-6; EN18, 20, 21 and 34; LA2, 4, 5, 7, 8, 11, 12, 14; SO3-8, 11; PR1-5, 7-9; HR3, 8-10.